Comparative bioavailability study of supplemental oral Sucrosomial® vs. oral conventional vitamin B12 in enhancing circulatory B12 levels in healthy deficient adults: a multicentre, double-blind randomized clinical trial - Memon, Nazia M.; Conti, Gabriele; Brilli, Elisa; Tarantino, Germano; Chaudhry, Muhammad N. A.; Baloch, Ameeran; Shafiq, Areaba; Mumtaz, Sami U.; Qaisar, Wafa; Iqtadar, Somia; Abrar, Saida; Kanwal, Ayesha; et al. (Frontiers in Nutrition, 2024)
Background: Vitamin B12 is essential for neurological function, red blood cell formation, and DNA synthesis. Deficiency can lead to diverse health conditions, including megaloblastic anemia and neurological issues. Oral supplementation is a standard treatment for B12 deficiency. The Sucrosomial® carrier system offers an innovative approach that enhances supplemental nutrient absorption and bioavailability. Objectives: This study aimed to compare the effectiveness of oral Sucrosomial® vitamin B12 formulation with various conventional B12 supplements, randomly selected from local pharmacies, in increasing and maintaining circulatory B12 levels in healthy deficient adults (200–300 pg/ml). Methods: A randomized, double-blind clinical trial was conducted across three centers in Pakistan from April to July 2024. At KEMU, participants received either Sucrosomial® vitamin B12 or Mecogen SL B12; at LRH, Sucrosomial® B12 or B-SUB B12; and at LUMHS, Sucrosomial® B12, Evermin B12, or Neuromax B12. Participants took a daily dose of 1000 µg of the assigned B12 formulation for 7 days. Serum B12 levels were measured at baseline (day 0) and on days 1, 3, 5, and 7. Results: Sucrosomial® B12 was significantly more effective than conventional B12 formulations in increasing and maintaining higher serum B12 levels across all time points. At KEMU, it reached a peak concentration of 454 ± 3.9 pg/ml by day 5, compared to 274 ± 11.1 pg/ml with Mecogen SL B12. At LRH, it peaked at 496 ± 34.4 pg/ml by day 5 versus 304 ± 49.4 pg/ml for B-SUB B12. At LUMHS, it reached 592.7 ± 74.3 pg/ml by day 7, compared to 407.24 ± 41.6 pg/ml for Evermin B12 and 263.82 ± 23.8 pg/ml for Neuromax B12. Sucrosomial® B12 was the only formulation to surpass the deficiency-borderline threshold (200-300 pg/ml) within 24 hours of the first dose and was well tolerated with no reported side effects. Conclusion: Sucrosomial® vitamin B12 demonstrated superior efficacy in rapidly and consistently elevating and maintaining higher circulatory B12 levels compared to conventional supplements. Its characteristic absorption mode and proven efficacy suggest it could effectively address B12 deficiency in a broad range of populations, including those with gastrointestinal conditions and pernicious anemia, thereby supporting overall health.